Usage of Colors in TV Commercials: Cross-Industry Analysis of Mass Media Communications - Gunina, Daria; Kincl, Tomas; Suldova, Sabina (Communications - Scientific letters of the University of Zilina, 2017)
The aim of this study is to analyze the differences in color schemes in TV commercials across different product categories. The study answers the question of whether advertisers in different industries use specific color schemes to promote their company or products in TV commercials and if they follow the general recommendations for using colors in marketing communications. The research sample consists of 200 video adverts proportionally representing the commercials aired in six major product categories in the Czech Republic in 2016. The results indicate there is no statistically significant difference in the usage of colors between the product categories. Nevertheless, the advertisers in the Czech Republic generally follow the color scheme recommendations suggested by the theory.